(3Gdbhd GdeTjO aj hba GdeDjOs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3hbY GdSDGd Yf hba Gdedc GdeDjO s
(3BNQgG (B:s
(3GfJgi hUdi Gddg Ydi SjOfG eMeOq s
(3Vef eLehY , JQJjHgG (B: 39s
(3YdjgG hba ddLGeY GdCYXe GdecJHI GdCMeOjI HJhfS HJGQjN (B1256 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B301 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B535s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1365s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
Keywords: (3Gdabg GdESdGejs